Fossils uncovering clues to the past - Raham, R. Gary; Superstone, Herb; Lorato, Rita (Fort Collins : Scott Resources Inc., 1993)
A contemporary look at how fossils reveal the story of life on Earth through millions of years of geologic time. This Teacher's Guide contains vocabulary words defined in the context of the video, discussion points, and classroom activities designed to enhance the videotape and create an interactive learning experience for students
Keywords: Paleontology